A systematic review of counterfeit and substandard medicines in field quality surveys - Alghannam AFA; Aslanpour Z; Evans S; Schifano F (Dove Medical Press, 2014)
Abdulaziz Fahad Abdulaziz Alghannam, Zoe Aslanpour, Sara Evans, Fabrizio Schifano Department of Pharmacy, University of Hertfordshire, Hatfield, Hertfordshire, United Kingdom Objectives: Counterfeit and substandard medicines pose a great threat to public health and the economy worldwide. Reports suggest their prevalence is increasing and can no longer be ignored. A detailed account on the current nature of the problem and identification of knowledge limitations in terms of geographical location, medicine classes, and type of medicine analysis performed is not available. Our objective was to systematically review articles that have reported investigations of counterfeit and substandard medicines. Design: Systematic review. Data sources: PubMed, Scopus, and ISI Web of Knowledge. Data Selection: Prospective field quality surveys on counterfeit and substandard medicines were selected from all available records within the selected databases up to December 31, 2013. All prospective studies performing chemical analysis on medicine samples were identified using the key search terms “counterfeit” or “substandard” and “medicine” or “drug” or “pharmaceutical.” The title, abstract, and/or full articles were reviewed for relevance according to a predetermined set of inclusion and exclusion criteria. Medicines procured from the Internet are beyond the scope of this review. Results: Sixty-six research articles were found that fulfilled our inclusion criteria. The majority of medicine quality surveys were conducted in specific areas of Africa and Asia. Within these two continents, medicine quality reports covering the Northern part of Africa and the Western part of Asia in the Middle East are extremely scarce. Other continents such as North or South America and Europe were covered in limited articles, whereas the Australian continent had no reports. Moreover, most studies examined medicines that treat infectious diseases; very few articles addressed popular medicines for chronic diseases or clinically significant narrow therapeutic index medicines or cancer treatments, despite media reports of quality problems in these medicines. Furthermore, only six (9%) research articles attempted all levels of medicine quality analysis available through laboratory analysis, authentication of source, and package inspection to comprehensively identify the nature of the problem and so conclude whether the medicines were counterfeit or substandard. Conclusion: Substandard and counterfeit medicines should be considered and identified through means of chemical analysis, physical analysis, authentication of source, and package inspection in any field medicine quality survey. More research is encouraged to examine the medicine quality in neglected parts of the globe and on neglected, yet popular and clinically significant, noncommunicable disease medicines. Keywords: counterfeit, substandard, poor quality, SSFFC, medicine and drug